(untitled) (Bangladesh Journal of Nuclear Medicine, 2022)
Subdiaphragmatic high renal ectopia and eventration of the diaphragm are unusual entities, and the combination of the two is extremely rare. We present a case of a young man with non-visualized left kidney in abdominal ultrasonography (USG). Static renal scan with 99mTc-DMSA showed an abnormally high, relatively smaller, and malrotated left kidney without any renal scarring. CT scan was also done to rule out possible associated abnormalities. It became evident that the left kidney was smaller and malrotated, lying posteriorly and much above the spleen and stomach as well, but immediately beneath the abnormally high left dome of the diaphragm at the level of the sixth rib. Apart from the abnormally high left dome, there were no other abnormalities seen in the diaphragm. The reported case of diaphragmatic eventration with high renal ectopia may be an important differential diagnosis of diaphragmatic rupture, a frequently encountered difficulty in clinical practice. Bangladesh J. Nuclear Med. 25(2): 151-153, 2022